(untitled) (ENTHYMEMA, 2025)
In the diamesic continuum from spontaneous speech to written language, many speech forms lack the unwilling responses and the reflex actions of face-to-face interaction. For instance, beyond reading aloud speech, the peculiarity typically regards formal public speech and acted speech. In fact, while in the spontaneous language performance, the ideational process is synchronous to the locutionary process, and speech goes on together with the flow of thought, in the reading, instead, the content is figured out completely only afterward, and also, for this reason, the performance frequently lacks communicative efficiency. The paper offers an overview of an innovative reading-aloud teaching practice based on an empiric multimodal approach in which visuospatial sensorimotor dynamic instructions exploit the capability of gestures and body movements to trigger a meaningful, effective text interpretation.